A porous Co–Ru@C shell as a bifunctional catalyst for lithium–oxygen batteries. Issue 42 (2nd July 2018) - Chen, Xiang; Zhang, Xiuhui; Chen, Chunguang; Huang, Tao; Yu, Aishui
Abstract : We use SiO2 as a template and dopamine as a carbon source to synthesize a hollow C shell, and we load Co and Ru nanoparticles onto it to obtain a Co–Ru@C shell composite. Abstract : We use SiO2 as a template and dopamine as a carbon source to synthesize a hollow C shell, and we load Co and Ru nanoparticles onto it to obtain a Co–Ru@C shell composite. The diameter and thickness of the C shell are 100 nm and 5–10 nm, respectively, and numerous holes of different sizes exist on the C shell. Meanwhile, numerous C shells stack together to form macropores, thereby forming a hierarchical porous structure in the material. Brunauer–Emmett–Teller surface area analysis reveals that the specific surface area and pore volume of the Co–Ru@C shell are 631.57 m 2 g −1 and 2.20 cc g −1, respectively, which can result in many three-phase interfaces and provide more space for the deposition of discharge products. Compared with Co@C shell and C shell electrodes, the obtained Co–Ru@C shell-based electrodes exhibit the highest discharge capacity, the lowest oxygen reduction reaction/oxygen evolution reaction overpotential and the best cycle stability, indicating the excellent catalytic ability of the Co–Ru@C shell.